THE EVALUATION OF PUBLIC SERVICES IN BAQUBAH CITY BY USING REMOTE SENSING & GIS TECHNIQUES - الهاشمي, د.محمد علي ابراهيم; صالح, د.صلاح عبدالحميد; حسين, امجد ناصر (Journal of Planner and Development, 2008)
Baqubah city has grown extremely rapidly. The rate of growth exceeds the growth of services that must grow side by side with the growth of population. There are natural features that affect the growth of Baqubah city such as Dieyala river, Alssariya river, in addition to agricultural areas .All these natural features affect the growth of Baqubah city in the running form being seen . In this research the remote sensing and geographic information system (GIS) techniques are used for monitoring urban expansion and forecasting the probable axes to the growth of the city, and found that the probability of Baqubah growth to east is preferred due to Baqubah growth to the east would never interfere with natural features. Also in this research the Baqubah public services are evaluated by building data base that attach spatial data with the descriptive data and then compared with the allowed standards for those services